2022
DOI: 10.1097/ico.0000000000003159
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Clinicians’ Diagnostic Uncertainty When Making Initial Treatment Decisions for Microbial Keratitis

Abstract: There is a need to understand physicians' diagnostic uncertainty in the initial management of microbial keratitis (MK). This study aimed to understand corneal specialists' diagnostic uncertainty by establishing risk thresholds for treatment of MK that could be used to inform a decision curve analysis for prediction modeling.Methods: A cross-sectional survey of corneal specialists with at least 2 years clinical experience was conducted. Clinicians provided the percentage risk at which they would always or never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…There are lots of anti-viral prescribing patterns currently, Cabrera-Aguas et al [ 164 , 165 ], described the need to standardize the indication and dosage of antiviral therapy in the management of HSK[ 164 , 165 ]. Ultimately, the decision to treat and treatment regimen selection is largely dependent on the individual clinician[ 166 ]. Lázaro-Rodríguez et al [ 167 ] reported isolated primary herpes-simplex virus neuroretinitis in an immunocompetent adult; thus, underpinning the need for starting antiviral therapy for individuals with macular stars who are not immunocompromised but seropositive for HSV IgM after ruling out other infectious causes, ionizing radiation, and arterial hypertension[ 167 ].…”
Section: Antiviral Therapy For Herpes Simplex Keratitis: Efficacy And...mentioning
confidence: 99%
“…There are lots of anti-viral prescribing patterns currently, Cabrera-Aguas et al [ 164 , 165 ], described the need to standardize the indication and dosage of antiviral therapy in the management of HSK[ 164 , 165 ]. Ultimately, the decision to treat and treatment regimen selection is largely dependent on the individual clinician[ 166 ]. Lázaro-Rodríguez et al [ 167 ] reported isolated primary herpes-simplex virus neuroretinitis in an immunocompetent adult; thus, underpinning the need for starting antiviral therapy for individuals with macular stars who are not immunocompromised but seropositive for HSV IgM after ruling out other infectious causes, ionizing radiation, and arterial hypertension[ 167 ].…”
Section: Antiviral Therapy For Herpes Simplex Keratitis: Efficacy And...mentioning
confidence: 99%
“…Timely diagnosis of MK and early prescribing of appropriate antimicrobials are imperative to increase the likelihood of a good patient outcome . However, bacterial and fungal MK cannot be distinguished by clinical presentation alone, and the current diagnostic strategy has several limitations . One limitation is the paucity of diagnostic tests suitable for use within community or primary health care settings .…”
Section: Introductionmentioning
confidence: 99%
“…6,[8][9][10][11] However, bacterial and fungal MK cannot be distinguished by clinical presentation alone, 12 and the current diagnostic strategy has several limitations. 13,14 One limitation is the paucity of diagnostic tests suitable for use within community or primary health care settings. 10 Lack of diagnostics in these settings is associated with reduced access to and engagement with the health care system, delays in presenting at tertiary care centers, increased economic burden to the patient (who typically has low socioeconomic status), and worse overall outcomes.…”
mentioning
confidence: 99%